HUBUNGAN DUKUNGAN EMOSIONAL KELUARGA DENGAN PENERIMAAN DIRI PADA LANSIA DI DESA WATUTUMOU III - Sangian, Liliyanti M L; Wowiling, Ferdinand; Malara, Reginus (Universitas Sam Ratulangi, 2017)
Abstract : Family support is a form of servant behavior performed by the family both in the form of emotional support, awards, information and instrumental. Self-acceptance of the elderly is a high appreciation or not being cynical about self-relating to the elderly's willingness to open up or express thoughts, feelings, and reactions to others and able to accept his shortcomings as well as his ability to accept the advantages. The purpose of this study to analyze The relationship between the emotional support of the family and the self-acceptance of the elderly in Watutumou Village III. The research method is analytical descriptive with cross sectional design. The sampling technique in this study is purposive sampling with the sample number of 60 respondents.The data collection is done by using a questionnaire and interview sheet. Processing data using computer program with Pearson chi-square test with a significance level of 95% (Î± =, 005). The results of this study using pearson chi-square analysis showed that there was a relationship between the emotional support of the family and the self-acceptance of the elderly in Watutumou III Village (p = 0,000). Conclusion There is a relationship between the emotional support of the family with self-acceptance in the elderly in Watutumou Village III. Keywords:emotional support of the family, the self-acceptance of the elderly Abstrak : Dukungan keluarga adalah suatu bentuk perilaku melayani yang dilakukan oleh keluarga baik dalam bentuk dukungan emosi, penghargaan, informasi dan instrumental.Penerimaan diri lansia merupakan penghargaan yang tinggi atau tidak bersikap sinis terhadap diri sendiri yang berkaitan dengan kerelaan lansia untuk membuka diri atau mengungkapkan pikiran, perasaan, dan reaksi terhadap orang lain serta mampu menerima kekurangan dirinya sebagaimana kemampuannya untuk menerima kelebihannya.Tujuan penelitian ini untuk menganalisahubungan antara dukungan emosional keluarga dengan penerimaan diri pada lansia di Desa Watutumou III. Metode penelitian yaitu deskriptif analitik dengan rancangan cross sectional. Teknik pengambilan sampel pada penelitian inipurposive samplingdengan jumlah sampel 60 responden. Pengumpulan data dilakukan dengan menggunakan kuesioner. Pengolahan data menggunakan program komputer dengan uji pearson chi-square dengan tingkat kemaknaan 95% (Î± = ,005). Hasil penelitian dengan menggunakan analisis pearson chi-square menunjukkan terdapat hubungan antara dukungan emosional keluarga dengan penerimaan diri pada lansia di Desa Watutumou III(p= 0,000). Kesimpulan terdapat hubungan antara dukungan emosional keluarga dengan penerimaan diri pada lansia di Desa Watutumou III. Kata kunci : Dukungan Emosional Keluarga, Penerimaan Diri Lansia